The Prospect, Legal, and Socio-economic Implication of Metaverse Operation in Nigeria - Paul Atagamen Aidonojie; Adesoji Kolawole Adebayo; Eregbuonye Obieshi; Antai Godswill Owoche; Isaac Ottah Ogbemudia; Muhammad Mutawalli (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The metaverse, a digital realm blending virtual environments with reality, holds immense potential across sectors. In Nigeria, understanding its implications necessitates exploration from various angles. Firstly, the legal landscape demands scrutiny, with existing regulations evaluated for their applicability and efficacy. Secondly, socio-economic considerations assume paramount importance, given the metaverse's potential to reshape societal norms and economic activities. Concerning this, the employ a hybrid research methodology that focus on the potentials of metaverse's emergence, legal framework, and socio-economic effects within Nigeria. 308 questionnaire were distribute to respondents residing in Nigeria. The collected data underwent descriptive and analytical analysis. The findings underscore that permitting the operation of the metaverse in Nigeria holds promise for enhancing the nation's economy and facilitating digital interactions. However, the study also reveals potential pitfalls notably that the existing legal framework may prove insufficient in addressing the unique challenges posed by the metaverse. Moreover, the metaverse's transformative impact on the Nigerian economy may carry adverse consequences. Consequently, the study concludes by recommending the imperative need for a novel legal framework tailored to address the distinctive intricacies presented by the metaverse for its effective operation in Nigeria.